A Protective Model for Suicidal Behaviors in American and Pakistani College Students. (May 2021) - Klibert, Jeffrey J.; Aftab, Sobia; Tarantino, Nicholas; Miceli, Matthew; Lamis, Dorian
There is a paucity of cross-national studies evaluating protective models for suicidal behaviors. Thus, using a behavioral framework, the purpose of this study was to examine whether higher levels of life-enhancing behaviors could mitigate or weaken the relation between depressive symptoms and suicidal behaviors in United States and Pakistani college students. A total of 811 students (449 Pakistani and 362 U.S. students) participated in the study. Results indicated that the strength of the relation between depressive symptoms and suicidal behaviors was stronger for U.S. students. In addition, the association between depressive symptoms and suicidal behaviors weakened in the presence of high engagement in life-enhancing behaviors. This effect was comparable in strength for American versus Pakistani students. The results offer preliminary evidence for life-enhancing behaviors as a protective factor for suicide across unique cultural settings and may serve as a valuable area of focus for secondary prevention programs.